Answer:
[tex]8+3x^2+7x+4[/tex]
Step-by-step explanation:
The first expression is
[tex]7+3x^2+7x+3[/tex]
The sum of the constants is 7+3=10
The sum of the coefficients is 3+7=10
The second expression is;
[tex]7+4x^2+4x+1[/tex]
The sum of the constants is 7+1=8
The sum of the coefficients is 4+4=8
The third expression is;
[tex]8+4x^2+8x+2[/tex]
The sum of the constants is 8+2=10
The sum of the coefficients is 4+8=12
The fourth expression is;
[tex]8+3x^2+7x+4[/tex]
The sum of the constants is 8+4=12
The sum of the coefficients is 3+7=10
Hence the correct choice is the expression in which the sum of the constants greater than the sum of the coefficients